PEMODELAN SPASIAL EPIDEMIOLOGI FASCIOLIASIS BERDASARKAN ANALISIS FAKTOR RISIKO SEBAGAI STRATEGI PENGELOLAAN TERNAK DI DAERAH ISTIMEWA YOGYAKARTA - Bramdito, Vandam Caesariadi; Hadibasyir, Hamim Zaky; Wardhani, Seandrasto Abi Kharis; Febriany, Rina; Hani, Ira Nurmala; Widayani, Prima (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The government’s efforts of the Special Region of Yogyakarta (Daerah Istimewa Yogyakarta/DIY) government for self-sufficiency in meat certainly have obstacles, one of which is the productivity of livestock development which is hampered by parasitic diseases such as Fascioliasis. Fascioliasis is a disease caused by F. hepatica or F. gigantica. To find out the relationship between risk factors for Fascioliasis disease in a spatial region, it can use spatial modeling by integrating remote sensing technology and Geographic Information Systems (GIS). Spatial modeling can be used to determine the correlation between risk factors and can also be integrated with secondary data to obtain more comprehensive information. The method used in this study is a combination of various quantitative methods consisting of data processing based on remote sensing and GIS for risk factor analysis. Besides, some variables are not obtained quantitatively, namely livestock management variables obtained by structured interviews with livestock owners and veterinary experts. In general, DIY has a moderate risk level for Fascioliasis parasites. Although there are common levels of risk, the conditions of vulnerability and vulnerability of the constituents may differ, which implies different livestock management strategies.